The un|common ground - Koutsomichalis, Marinos (My University, 2022)
Our individual research areas overlap in decolonial, non-western, and off-center language-informed/language-driven and poetic practices. How do languages embed, implement, and help establish colonial regimes and how may these be challenged and resisted through language? How can we use language to creatively articulate decolonial concerns? Can language become some kind of sanctuary? A hiding place wherein borderland and non-dominant (micro-)cultures may dwell and thrive? How can non-western languages and off-center references set out new directions for artistic research and practices? What happens when such off-centered – strictly non-western, non-dominant, queer or feminist – local points of reference intersect and inform one another? What is the relationship between language (embodied, oral, and written) and community-forming, ununderstandability, untranslatability, and opacity? We reflect on these and other questions against the backdrop of our research practices and poetic/literary projects.
Keywords: Decolonial; Languages